Klasterisasi Perguruan Tinggi Swasta di Madura Berdasarkan Kinerja Sumber Daya Manusia dan Mahasiswa Menggunakan Metode K-Means Clustering - Yuli Sasmita; Muhsi Muhsi; Miftahul Walid (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The number of private universities in Indonesia in 2020 is 3,044 private universities, in East Java 328 private universities and in Madura 30 private universities. The number of private universities in Indonesia causes intense competition. Colleges should strive to maintain and improve performance in order to ensure their activities. Therefore, it is necessary to do or group private universities based on the performance of human resources and students to encourage these universities to improve their performance. The grouping of private universities is carried out using the k-clustering method which groups data into several clusters based on data groups which are. The results of this study, the grouping of private universities in Madura into 3 clusters, namely: Cluster 1 there are 4 private universities, Cluster 2 there are 7 private universities, and Cluster 3 there are 19 private universities.